2006
DOI: 10.1074/jbc.m511608200
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Is Required for Haloperidol-induced Catalepsy in Mice

Abstract: Fyn-mediated tyrosine phosphorylation of N-methyl-D-aspartate (NMDA) receptor subunits has been implicated in various brain functions, including ethanol tolerance, learning, and seizure susceptibility. In this study, we explored the role of Fyn in haloperidolinduced catalepsy, an animal model of the extrapyramidal side effects of antipsychotics. Haloperidol induced catalepsy and muscle rigidity in the control mice, but these responses were significantly reduced in Fyn-deficient mice. Expression of the striatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Another D2R antagonist haloperidol was injected at a dose of 1 mg/kg calculated as the salt. This dose was chosen because haloperidol at this dose (1 h prior to brain tissue collection) increased tyrosine phosphorylation of several proteins in the mouse striatum (Hattori et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Another D2R antagonist haloperidol was injected at a dose of 1 mg/kg calculated as the salt. This dose was chosen because haloperidol at this dose (1 h prior to brain tissue collection) increased tyrosine phosphorylation of several proteins in the mouse striatum (Hattori et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…6A). The D2 antagonist L-741,626 (30 mM; Hattori et al, 2006) blocked the 10 mM quinpirole effect (not shown), demonstrating that this effect is mediated by D2 receptor activation. In the presence of the D2 antagonist, we still observed a slight decrease of NMDA currents (213.4 6 3.4%, n 5 4).…”
Section: Effects On [mentioning
confidence: 99%
“…In situ hybridization was performed using a digoxigenin (DIG)-labeled full-length Epc1 cRNA probe. Staining procedures were carried out as previously reported (37). Briefly, adult male ICR mice were fixed by transcardiac perfusion with 4% paraformaldehyde in 0.1 M sodium…”
Section: Methodsmentioning
confidence: 99%